Reporte de caso: Leiomioma cervical y tumor mamario en canino de raza mestiza (2016)
It is report and describes the development of clinical case of a dog of mixed breed of 10-year-old, who presented the protrusion of part of genital tissue, with bloody discharge decreased, smooth texture, edemetizada without the presence of tenderness, this picture was accompanied by the beginning of the reproductive stage (oestrus). Besides this, the patient had the presence of masses in breast area, according to anamnesis were from about 12 months. Made physical patient assessment, basic tests such as blood count, blood chemistry (ALT, BUN and creatinine) and complementary as histopathology are performed. As treatment of these pathologies a surgical approach is performed, in order to remove the protruded tissue, neoplastic tissue and breast ovariohysterectomy, choosing to complete reproductive apparatus corresponding histopathology to distinguish the source or type of neoplasia (benign or malignant). After interpreted the histopathology, the result was related to: cervical leiomyoma, cysts of Naboth, bilateral follicular cysts and cyst paratubario side unspecified, which are tumors formed from mesothelial tissue, with benign type and resolved simply by the performing surgical procedure named above. After treatment, the patient had a good recovery, besides not having recurrence of these diseases.